(untitled) (Materiali di Estetica. Terza serie, 2020)
Giovanni Piana’s phenomenology of music was directed against any conventionalist point of view about the musical experience. According to Piana, each compositional system depends on the phenomenological structure of sound that determines the musical perception. Tonal system is not prescribed by natural laws, however it is based on the essential difference between consonance and dissonance. So the perceptual meaning of a tonal piece is not founded on subjective (culturally acquired) habitudes, but on phenomenological data.